EFFECT OF GESTATIONAL DIABETES ON MICROANATOMY OF PLACENTA (Journal of Forensic Medicine & Toxicology, 2015)
Placenta is the vital organ of intrauterine life, undergoing both morphological and histological changes during pregnancy. The placenta facilitates embryogenesis, growth, maturation and survival of fetus. Adverse conditions like Gestational Diabetes and Hypertension, leads to destruction to placental architecture, ultimately affecting the outcome of pregnancy. This study was conducted with the sole aim to find out the histological changes in placentae procured from mother’s with gestational diabetes. It was found that there were significant histological changes in the placenta, which leads to detrimental effects on the fetus due to impaired fetal oxygenation and altered placental development
Keywords: Gestational Diabetes; Chorionic villi; Fibrosis; Fibrinous material; Obliterative endarteritis